PERLINDUNGAN HUKUM PEKERJA TAMBANG GALIAN TANAH ILEGAL STUDI KASUS DI PARUNG PANJANG: Legal Protection For Illegal Soil Mining Workers In Parung Panjang - Putri Mutaqiah; Andari Yurikosari (Reformasi Hukum Trisakti, 2025)
Illegal mining has become a complex phenomenon, involving low-income and poorly educated communities as mine workers. This practice poses high risks to workers, both in terms of occupational safety and environmental impact. The conducted study aims to examine the form of legal protection for workers in illegal soil excavation mining based on the applicable laws and regulations, particularly Law Number 13 of 2003 concerning Manpower. Additionally, the research problem in this case focuses on the protection of workers in illegal mining operations and the employer's responsibility in the event of work-related accidents, such as the case of a miner's death in Parung Panjang. The research employs a normative legal approach, supported by field studies to obtain empirical data. The findings and conclusions indicate that workers in illegal mining operations do not receive adequate protection. Cultural factors and the economic dependence of local communities exacerbate the situation, making it difficult to enforce legal regulations. The study recommends an active role of the government in supervising and regulating illegal mining operations, as well as the need for socialization on the importance of occupational safety and simplified licensing processes to provide better protection for workers.